Optoelectronic Devices: Thin Metallic Heat Sink for Interfacial Thermal Management in Biointegrated Optoelectronic Devices (Adv. Mater. Technol. 11/2018). Issue 11 (16th November 2018) - Jung, Han Hee; Song, Juwon; Nie, Shuang; Jung, Han Na; Kim, Min Seok; Jeong, Jae‐Woong; Song, Young Min; Song, Jizhou; Jang, Kyung‐In
Abstract : In article number1800159, Young Min Song, Jizhou Song, Kyung‐In Jang, and co‐workers develop a bio‐integrated optoelectronic device with integration of thin metallic heat sink for interfacial thermal management. It exhibits excellent heat dissipation capabilities for thermally safe long‐term usability, due to the high thermal conductivity and film‐type geometrical design of the heat sink for skin applications. The architecture of the device with the metallic heat sink ensures mechanically and thermally invisible blood flow monitoring.